Lipid-Encapsuled Grape Tannins Prevent Oxidative-Stress-Induced Neuronal Cell Death, Intracellular ROS Accumulation and Inflammation - Diaz, Hugo S.; Rios-Gallardo, Angelica; Ortolani, Domiziana; Diaz-Jara, Esteban; Jose Flores, Maria; Vera, Ignacio; Monasterio, Angela; Ortiz, Fernando C.; Brossard, Natalia; Osorio, Fernando; Del Rio, Rodrigo (My University, 2022)
The central nervous system (CNS) is particularly vulnerable to oxidative stress and inflammation, which affect neuronal function and survival. Nowadays, there is great interest in the development of antioxidant and anti-inflammatory compounds extracted from natural products, as potential strategies to reduce the oxidative/inflammatory environment within the CNS and then preserve neuronal integrity and brain function. However, an important limitation of natural antioxidant formulations (mainly polyphenols) is their reduced in vivo bioavailability. The biological compatible delivery system containing polyphenols may serve as a novel compound for these antioxidant formulations. Accordingly, in the present study, we used liposomes as carriers for grape tannins, and we tested their ability to prevent neuronal oxidative stress and inflammation. Cultured catecholaminergic neurons (CAD) were used to establish the potential of lipid-encapsulated grape tannins (TLS) to prevent neuronal oxidative stress and inflammation following an oxidative insult. TLS rescued cell survival after H2O2 treatment (59.4 +/- 8.8% vs. 90.4 +/- 5.6% H2O2 vs. TLS+ H2O2; p < 0.05) and reduced intracellular ROS levels by similar to 38% (p < 0.05), despite displaying negligible antioxidant activity in solution. Additionally, TLS treatment dramatically reduced proinflammatory cytokines' mRNA expression after H2O2 treatment (TNF-alpha: 400.3 +/- 1.7 vs. 7.9 +/- 1.9-fold; IL-1 beta: 423.4 +/- 1.3 vs. 12.7 +/- 2.6-fold; p < 0.05; H2O2 vs. TLS+ H2O2, respectively), without affecting pro/antioxidant biomarker expression, suggesting that liposomes efficiently delivered tannins inside neurons and promoted cell survival. In conclusion, we propose that lipid-encapsulated grape tannins could be an efficient tool to promote antioxidant/inflammatory cell defense.
Keywords: oxidative stress; polyphenols; liposomes; neuroprotection; natural products